EFEKTIVITAS DAN PENERAPAN KUASA DALAM AKTA PENGIKATAN/ PERJANJIAN JUAL BELI ATAS OBJEK TANAH SERTA KETERKAITANNYA DENGAN AKTA KUASA JUAL - Herry Santoso (PREMISE LAW JURNAL, 2013)
ABSTRACT Purchase contract on land rights is a legal action made by parties (in this case, a seller and a purchaser) in which the seller wants to sell his land plus the properties on it to the purchaser who makes an agreement to purchase the seller’s land and all properties on it but without definitive contract since it is not made before the PPAT (official empowered to draw up land deeds). In this case, the purchase contract made before the Notary constitutes the preliminary agreement prior to the requirements for definitive purchase contract made before the PPAT are fulfilled. What it means by requirements is that the seller’s documents on the land are not complete yet or the process of buy and sell is in installment. In this case, the process of buy and sell cannot be conducted before the PPAT, and the power of attorney from the seller to the purchaser cannot be made since the documents are not complete or it is in installment. A purchase contract is closely related to giving the power of attorney and the proxy deed by the seller to the purchaser; therefore, in the purchase contract it is usually called preliminary contract or the delay of purchase contract while waiting for the fulfillment of all requirements in the purchase contract by both parties.     Kata kunci: Purchase Contract, Land, Proxy Deed for Selling